Peningkatan Efektifitas Layanan TPS Di Kelurahan Renon Melalui Post Pelayanan Bantu Masyarakat - Wardani, Kadek Devi Kalfika Anggria; Darmayanti, Desy; Wulandari, Ni Gusti Agung Ayu Mas Tri (LPPM Universitas Timor, 2024)
Renon Subdistrict frequently experiences long queues at polling stations (TPS) during elections. One contributing factor to this issue is that 50% of the community does not receive the C-notification letter. Ultimately, this problem leads to delays in the completion of elections in Renon Subdistrict. In response to these findings, the proposed solution from the service team is to establish a Community Assistance Service Post. The Community Assistance Service Post functions as a place where residents can check whether they are registered on the voter list (DPT) and are eligible to vote in Renon Subdistrict. The goal is to prevent long queues and reduce abstentions caused by residents who do not receive the C-notification letter. The method used in this community service activity is descriptive analysis with a qualitative approach involving interviews with relevant stakeholders, literature studies, and field observations. The result of this service is the prevention of long queues during elections and a reduction in voter abstention. Recommendations include collaborating with internet service providers for network support and continuing to improve the Community Assistance Service Post in future elections.